Dietary UKMR-1 Roselle supplementation prevents nicotine-induced cardiac injury by inhibiting myocardial oxidative stress - Anand Ramalingam,; Siti Balkis Budin,; Lim, Yi-Cheng; Si, Yiang-Lislivia Nee; Satirah Zainalabidin, (Penerbit Universiti Kebangsaan Malaysia, 2016)
UKMR-1, a local variant of mutant Roselle strain (Hibiscus sabdariffa) is enriched with free radical scavenging polyphenols such as anthocyanin, vitamin C and hydroxycitric acid. However, pharmacological actions of UKMR-1 are not fully known. This study was conducted to determine whether supplementation of aqueous UKMR-1 calyx extract was able to protect against nicotine-induced cardiac injury in rats. In this experimental study, healthy male albino rats were randomly allotted into three groups (n=7 per group): control, nicotine and UKMR-1+Nicotine groups. Nicotine (0.6 mg/kg, i.p.) was administered to both nicotine and UKMR-1+Nicotine groups for 28 consecutive days. UKMR-1+Nicotine group also received 100 mg/kg UKMR-1 extract orally via gavage 30 min prior to nicotine injection, daily. UKMR-1+Nicotine group had significantly (p<0.05) higher lactate dehydrogenase (LDH) activity, as well as lower malondialdehyde content in heart tissue homogenate than nicotine group, suggesting its cardio protective activity by inhibition of lipid peroxidation. UKMR-1 also lowered (p<0.05) the blood pressure in nicotine-administered rats. In addition, UKMR-1 significantly (p<0.05) restored activities of cytosolic superoxide dismutase, glutathione peroxidase and glutathione-S-transferase as well as redox balance ratio (GSH:GSSG). In conclusion, UKMR-1 was able to protect against myocardial injury in rat model of nicotine administration possibly by inhibiting oxidative stress.